Citizens in Distress: A Case Study on Public Participation During the Covid‐19 Pandemic in Finland - Värttö, Mikko (Cogitatio, 2025)
In emergencies, public participation can perform a positive function by raising public awareness of the potential harms and injustices that may have resulted from emergency measures and policies. In this way, public participation can contribute to democratic crisis management, and also legitimise democratic
institutions more broadly. However, emergency conditions can challenge these participatory practices, undermining citizens’ ability to influence crisis management. To investigate this phenomenon, this article studies how ordinary citizens participated in the management of the Covid‐19 pandemic. The article focuses on Finland, a critical case because its response to the pandemic is often considered successful in international comparison. In the analysis, data on various formal and informal forms of public participation are considered and their impact on emergency response is assessed. The findings show that although multiple forms of public participation were in place, the authorities used them selectively and hesitantly.
Also, public participation was often diminished to an advisory role or channelled through established civil society actors, such as labour market organisations. Due to this lack of critical voices in public arenas, citizens decided to bypass formal routes of public participation to express their concerns through civic activism in informal channels. These concerns materialised in campaigns, protests, and demonstrations against emergency measures and policies. While much of the existing literature focuses on the negative effects of civic activism, such as spreading misinformation and undermining official measures, this article argues that informal public participation, such as civic activism, can complement formal decision‐making
measures during emergencies, thus contributing to more effective and democratic crisis governance.